Assessment of performance and diversity of Lemongrass cultivars (Cymbopogon spp.) cultivated in the foot hills of Himalayan Riverbeds - Tomar, Jag Mohan Singh; Barh, Anupam; Rawat, Deepika; Kaushal, Rajesh; Annepu, Sudheer Kumar; Varshney, V. K.; Madhu, M. (Frontiers in Agronomy, 2025)
IntroductionLemongrass (Cymbopogon spp.) is an aromatic grass species known for its adaptability to a wide range of agro-climatic conditions. Degraded lands, such as riverbed is present challenges for conventional agriculture. This study aimed to investigate the potential for lemongrass cultivars in riverbed lands at Dehradun.MethodsThe experiment was conducted at ICAR-IISWC Dehradun from 2014 to 2018 on degraded riverbeds. Eight lemongrass cultivars—Cauvery, Chirharit, CIM-Suwarna, CIM-Shikar, Krishna, Parman, Pragati, and Nima—were selected for evaluation. The cultivars were assessed for morphological parameters. Volatile oil was extracted and analyzed using Gas Chromatography–Mass Spectroscopy (GC-MS) to identify chemical constituents and study chemo-diversity among the cultivars. Genetic variability and diversity were also assessed.ResultsThe Krishna cultivar recorded the highest herbage yield, followed by Pragati. Krishna also exhibited the highest volatile oil content at 0.55%, with Pragati showing the second-highest value. GC-MS analysis identified Citral is the major constituent of lemongrass with maximum content in the cv. CIM Suwarna (51.67%). Chemo-diversity analysis revealed that, 6-methyl-5-Hepten-2-one, beta Myrcene, (3E)-3,7-dimethylocta-1,3,7-triene, 3,7-dimethyl- 1,3,6-Octatriene, Linalool, Isoneral, 3,6-Octadienal, 3,7-dimethyl, Citronellal, Neral, Geraniol, Citral, and Geranyl acetate are the common constituents found in all the cultivars and also revealed the cultivar specific compounds such as linoelaidic acid in cv. Chirharit; octadecanoic acid in cv. Cauvery and exocitral in cv. Cauvery, CIM-Shikar Krishna, Parman and Pragati. Data on genetic variability indicated that, total volatile oil content and herbage yield traits exhibited the maximum environment coefficient of variation suggesting significant influence from the growing conditions. The experimental findings suggested that the Krishna cultivar is suitable for degraded environmental conditions, thereby contributing to the land degradation neutrality commitments.